2013
DOI: 10.1093/cid/cit675
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Occurrence of Antimicrobial-Resistant Hypervirulent (Hypermucoviscous) Klebsiella pneumoniae Isolates in China

Abstract: HvKP strains are being isolated from patients in China with increasing frequency and constitute an increasing proportion of K. pneumoniae strains, indicating an increasing propensity for the acquisition of antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
237
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(262 citation statements)
references
References 37 publications
18
237
6
1
Order By: Relevance
“…The use of 48 hours as a cut-off for diagnosing nosocomial infections was arbitrary and could led to an overestimation of nosocomial infections. However, the frequency of community acquired hvKP infections in our patients was similar to that reported from other centers [26].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The use of 48 hours as a cut-off for diagnosing nosocomial infections was arbitrary and could led to an overestimation of nosocomial infections. However, the frequency of community acquired hvKP infections in our patients was similar to that reported from other centers [26].…”
Section: Discussionsupporting
confidence: 91%
“…hvKP isolates comprised 7.5% of all KP isolates from our hospital, 60% of which were associated with infection. We identified hvKP more frequently in urine and abscess, and less frequently in blood, tracheal secretion, and bile than another similar large hospital in China [26]. Most community-acquired infections were blood infections or a presence of different abscess, similar to previous reports [12,16,27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, although antibiotic resistance is a phenomenon associated primarily with classical K. pneumoniae, there have been reports of HV K. pneumoniae strains that carry ESBLs or carbapenemases (45,46). One recent study in China found ESBLs in 56% of classical K. pneumoniae strains compared to 17% of HV K. pneumoniae strains (47).…”
Section: Classical Antibiotic-resistant Emerging and Hypervirulentmentioning
confidence: 99%
“…For example, increased glucose concentrations result in the upregulation of capsule production though RmpA, while relatively high extracellular iron concentrations result in the downregulation of capsule production. In fact, 55 to 100% of HV K. pneumoniae strains express at least one copy of rmpA or rmpA2, compared to 7 to 20% of non-HV K. pneumoniae strains (47,214). These genes positively regulate the cps locus at the transcriptional level, resulting in the hypercapsule phenotype (202,(215)(216)(217).…”
Section: Capsulementioning
confidence: 99%